Public Acceptance and Institutional Trust in Nuclear Energy Transition Policies in Indonesia - Muhammad Faisal Akbar; Suhaidar; Nur Ahmad Ricky Rudianto; Rulyanti Susi Wardhani (Faculty of Economics, Universitas Sriwijaya, 2026)
This study investigates how socioeconomic characteristics and governance perceptions influence public acceptance of Indonesia’s energy transition, with a particular focus on nuclear energy and institutional trust. As Indonesia moves to reduce fossil-fuel dependence and diversify its energy mix, public support becomes critical to the legitimacy and implementation of transition policies. Using survey data from 189 residents of the Bangka Belitung Islands, this study applies a Probit regression model to estimate the effects of age, education, income, and governance-related perceptions, including regulatory compliance, political influence, and freedom of expression. The results show that age has a statistically significant negative effect on acceptance, indicating that older individuals are less likely to support nuclear energy development. By contrast, respondents who perceive government institutions as more compliant with regulations and more responsive to public concerns are more likely to support the transition. Other socioeconomic variables show limited explanatory power. These findings suggest that institutional trust and governance quality are more influential than socioeconomic status in shaping public acceptance of nuclear energy in Indonesia’s energy transition context.